Formulaic Language and EFL Requests: Sensitive Wording at the Right Time - Gerrard Mugford (Universidad Nacional de Colombia, 2017)
I examine whether teaching formulaic language raises English as a foreign language learners' awareness of pragmatic resources when expressing requests. To carry out this research I adopt a qualitative self-reflective approach which encourages students to use formulaic language when making requests. By responding to discourse completion tasks, learners were given the opportunity to reflect on whether the use of formulaic language enhances their ability to come across in acceptable and appropriate ways. Results indicate that by developing learners' knowledge and via the use of pragmalinguistic and sociopragmatic resources, students at all levels have a much greater chance of achieving their communicative objectives and of becoming more pragmatically competent in the target language when making requests.